2022
DOI: 10.1177/0271678x221145090
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin released from microglial lysosomes reduces neuronal ferroptosis after cerebral ischemia in mice

Abstract: The cellular redox state is essential for inhibiting ferroptosis. Progranulin (PGRN) plays an important role in maintaining the cellular redox state after ischemic brain injury. However, the effect of PGRN on ferroptosis and its underlying mechanism after cerebral ischemia remains unclear. This study assesses whether PGRN affects ferroptosis and explores its mechanism of action on ferroptosis after cerebral ischemia. We found endogenous PGRN expression in microglia increased on day 3 after ischemia. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Sample sizes for animal studies were determined by a two-sided power analysis for the primary parameter with mean differences and standard deviations based on similar previously published results (power ¼ 80%, a ¼ 0.05). 24,25 All statistics were performed using Prism GraphPad 9 (GraphPad Software, San Diego, CA). Results were presented as meanAEstandard deviation (SD).…”
Section: Discussionmentioning
confidence: 99%
“…Sample sizes for animal studies were determined by a two-sided power analysis for the primary parameter with mean differences and standard deviations based on similar previously published results (power ¼ 80%, a ¼ 0.05). 24,25 All statistics were performed using Prism GraphPad 9 (GraphPad Software, San Diego, CA). Results were presented as meanAEstandard deviation (SD).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ting Chen et al. reported that PGRN upregulation attenuated ferroptosis by decreasing malondialdehyde and increasing Gpx4, Nrf2, and Slc7a11 expression and glutathione levels in microglia ( 31 ). Although the function of PGRN in the progression of RA is not fully understood, we can speculate that PGRN may influence RA progression by attenuating ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased risk of RA and joint destruction in PGRN -/mice model of collageninduced arthritis compared to controls, and inflammatory arthritis can be revered by the administration of PGRN (25,29,30). Recently, Ting Chen et al reported that PGRN upregulation attenuated ferroptosis by decreasing malondialdehyde and increasing Gpx4, Nrf2, and Slc7a11 expression and glutathione levels in microglia (31). Although the function of PGRN in the progression of RA is not fully understood, we can speculate that PGRN may influence RA progression by attenuating ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies support the pro-ferroptotic role of lysosomes, specific lysosomal proteins or degradation products, such as cysteine and selenium, can also exert inhibitory effects on ferroptosis. GRN (granulin precursor), derived from microglial lysosomes, inhibits ferroptosis-mediated neuronal injury by upregulating the expression of GPX4, NFE2L2, and SLC7A11 [ 192 ]. In contrast, the knockdown of LAMP2A , a receptor for CMA, induces ferroptosis in retinal pigment epithelial cells by depleting cytosolic cysteine and GSH levels [ 193 ].…”
Section: Role Of Lysosomes In Ferroptosismentioning
confidence: 99%